2017
DOI: 10.1080/14767058.2017.1404983
|View full text |Cite
|
Sign up to set email alerts
|

Risk of donor demise after laser therapy for twin–twin transfusion when complicated by growth discordance and abnormal umbilical artery Doppler findings*

Abstract: Preoperative abnormal donor UAD is a significant risk for donor demise post-laser therapy for TTTS. Persistent postoperative abnormal UAD with concomitant growth discordance confers the greatest risk for donor demise. However, resolution of abnormal UAD has a similar rate of donor demise when compared to patients with normal UAD preoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…The reported rate of donor demise after SLPCV in all TTTS stages ranges from 11 to 28% [5,[8][9][10]. Previous studies have found Quintero stage III [5], UA-AEDV [7,9,12,14], UA-REDV [6-9, 12, 14], low EFW [10], fetal growth restriction [5], EFW discordance [6][7][8][9], early…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The reported rate of donor demise after SLPCV in all TTTS stages ranges from 11 to 28% [5,[8][9][10]. Previous studies have found Quintero stage III [5], UA-AEDV [7,9,12,14], UA-REDV [6-9, 12, 14], low EFW [10], fetal growth restriction [5], EFW discordance [6][7][8][9], early…”
Section: Discussionmentioning
confidence: 99%
“…Because of the documented association between percent EFW (%EFW) discordance and AEDV [7,9], we performed a similar but stratified set of analyses for those with and without fetal weight discordance, defined as preoperative %EFW discordance ≥20 versus < 20%. %EFW discordance was calculated as 100 × (EFW of larger twin -EFW of smaller twin)/EFW of larger twin.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations